Chitosan-curcumin nano-composite preservative and preparation method thereof
By constructing a chitosan-sodium alginate-oxidized sodium alginate ternary interpenetrating network, and utilizing electrostatic interactions, Schiff base chemical cross-linking, and zinc ion coordination mechanisms, the problems of poor structural stability of nanocarriers and low encapsulation efficiency of active ingredients were solved, resulting in a highly efficient and stable nanocomposite preservative suitable for various food preservation processes.
Patent Information
- Application Number
- CN202511504313.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2025-12-19
AI Technical Summary
Existing nanocarriers suffer from poor structural stability, low encapsulation efficiency of active substances, and limited application forms. Furthermore, the dispersibility and encapsulation efficiency of hydrophobic active substances in hydrophilic matrices need to be improved.
A chitosan-sodium alginate-oxidized sodium alginate ternary interpenetrating network was constructed, forming a stable nanoparticle structure through a triple mechanism of electrostatic interaction, Schiff base chemical crosslinking, and zinc ion coordination. Curcumin and epigallocatechin gallate form a complex through hydrogen bonding and hydrophobic interaction, which is embedded in the network and achieves efficient loading through zinc ion chelation coordination.
It significantly improves the structural stability of nanoparticles and the encapsulation rate of curcumin, enhances antioxidant activity, provides diverse application forms, and meets the needs of various preservation treatments such as spraying, coating, and soaking, while complying with food safety standards.
Abstract
Description
Technical Field
[0001] The invention relates to the field of food preservation materials technology, specifically to a chitosan-curcumin nanocomposite preservative and its preparation method. Background Technology
[0002] Developing efficient and safe food preservation technologies is of great significance. Biomolecular-based nanocarriers have attracted widespread attention in the food preservation field due to their advantages such as good biocompatibility and strong biodegradability. Chinese patent application CN116023716A discloses a layered nanoparticle-filled preservation-indicator composite film. This technology uses zein as a carrier, prepares indicator-protein nanoparticles through an antisolvent precipitation method, then adsorbs preservative factors onto the surface of the nanoparticles via hydrogen bonding, and finally adsorbs polysaccharides onto the outer layer of the protein nanoparticles through electrostatic attraction, forming a layered self-assembled structure.
[0003] However, this technology has the following shortcomings. First, the layer-by-layer assembly structure built solely through physical adsorption has limited stability and is prone to leakage of active ingredients during storage and application. Second, protein carriers tend to aggregate in a neutral to weakly acidic pH range, affecting the dispersibility and stability of nanoparticles. Third, this technology disperses nanoparticles in a thin film matrix, limiting its application and failing to meet diverse preservation needs such as spraying and soaking. Furthermore, the dispersibility and encapsulation efficiency of hydrophobic active ingredients such as curcumin in hydrophilic matrices still need improvement.
[0004] Therefore, there is an urgent need to develop a nanocomposite preservative with stable structure, high encapsulation efficiency, and flexible application forms to overcome the shortcomings of existing technologies. Summary of the Invention
[0005] The purpose of this invention is to provide a chitosan-curcumin nanocomposite preservative and its preparation method, so as to solve the technical problems of poor structural stability of nanocarriers, low encapsulation efficiency of active ingredients, and limited application forms in the prior art.
[0006] To achieve the above objectives, the technical solution adopted in this invention is to construct a chitosan-sodium alginate-sodium oxidized alginate ternary interpenetrating network structure, which is solidified through a triple mechanism of electrostatic interaction, Schiff base chemical crosslinking, and zinc ion coordination. Specifically, the protonated amino groups of chitosan and the carboxyl groups of sodium alginate form a polyelectrolyte complex core through electrostatic interaction. The aldehyde groups of sodium oxidized alginate react with the amino groups of chitosan through a Schiff base reaction to form a chemical crosslinking network. Zinc ions simultaneously form coordination crosslinks with the amino groups of chitosan, sodium alginate, and the carboxyl groups of sodium oxidized alginate. Curcumin and epigallocatechin gallate form a complex through hydrogen bonding and hydrophobic interaction. The complex is embedded in the interpenetrating network structure. The β-diketone group of curcumin further forms chelate coordination with zinc ions, achieving efficient loading and stable anchoring of the active ingredient.
[0007] This invention discloses a chitosan-curcumin nanocomposite preservative, comprising nanoparticles with an interpenetrating network structure of chitosan-sodium alginate-sodium oxidized alginate. The nanoparticles form a polyelectrolyte complex core through a Schiff base reaction between the protonated amino groups of chitosan and the carboxyl groups of sodium alginate. The aldehyde groups of sodium oxidized alginate react with the amino groups of chitosan to form a chemical cross-linking network. Zinc ions form coordination cross-links with the amino groups of chitosan, the carboxyl groups of sodium alginate, and the carboxyl groups of sodium oxidized alginate. Curcumin and epigallocatechin gallate form a complex through hydrogen bonding and hydrophobic interactions. The complex is embedded in the interpenetrating network structure, and the β-diketone groups of curcumin form chelate coordination with zinc ions.
[0008] In one embodiment of the present invention, the degree of deacetylation of the chitosan is 85% to 95%, and the molecular weight is 100 kDa to 300 kDa; the molecular weight of the sodium alginate is 200 kDa to 500 kDa; and the degree of oxidation of the oxidized sodium alginate is 20% to 30%.
[0009] In one embodiment of the present invention, the mass ratio of chitosan to sodium alginate is 1.0:0.5 to 2.0:1.0; the molar ratio of aldehyde groups to chitosan amino groups in the oxidized sodium alginate is 1:15 to 1:10; the molar ratio of zinc ions to chitosan amino groups is 0.1:1 to 0.3:1; and the mass ratio of curcumin to epigallocatechin gallate is 1.5:1 to 2.0:1.
[0010] In one embodiment of the present invention, the nanoparticles have a particle size of 150nm-300nm, a zeta potential of +25mV to +35mV, a curcumin encapsulation efficiency of ≥85%, an epigallocatechin gallate encapsulation efficiency of ≥75%, a curcumin loading of 8%-12%, and an epigallocatechin gallate loading of 5%-8%.
[0011] In one embodiment of the present invention, the preservative is a spray-dried powder with a moisture content of less than or equal to 5%, and trehalose is added as a cryoprotectant. The mass ratio of trehalose to solids is 1:3 to 1:5, and the nanoparticle size increases by no more than 20% after the powder is rehydrated.
[0012] The preparation method of the above-mentioned chitosan-curcumin nanocomposite preservative includes the following steps: Step 1: Dissolve curcumin in anhydrous ethanol and sonicate to obtain curcumin ethanol solution; dissolve epigallocatechin gallate in deionized water and heat to obtain epigallocatechin gallate aqueous solution; add the curcumin ethanol solution dropwise to the epigallocatechin gallate aqueous solution under stirring to form curcumin-epigallocatechin gallate nano precursor dispersion. Step 2: Disperse chitosan powder in deionized water, add glacial acetic acid and stir to dissolve, adjust the pH value to 5.0-5.5, add Tween 80 and stir to mix, to obtain chitosan solution; Step 3: Dissolve sodium oxidized alginate in deionized water and stir until completely dissolved to obtain sodium oxidized alginate solution; Step four: Sodium alginate is dissolved in deionized water to obtain a sodium alginate solution; zinc sulfate is dissolved in deionized water to obtain a zinc sulfate solution; under stirring conditions, the chitosan solution is added dropwise to the sodium alginate solution to form a polyelectrolyte complex nanocore; the curcumin-epigallocatechin gallate nanoprecursor dispersion is added to the polyelectrolyte complex nanocore; then the oxidized sodium alginate solution is added to carry out a Schiff base reaction; finally, zinc sulfate solution is added to carry out coordination crosslinking, and the reaction is stirred to obtain a nanoparticle suspension; Step 5: Centrifuge the nanoparticle suspension to collect the precipitate, wash it with deionized water, resuspend it in deionized water, add trehalose and stir to mix. Step six: Spray dry the trehalose-containing nanoparticle suspension and collect the dried powder.
[0013] In one embodiment of the present invention, in step one, the mass-to-volume ratio of curcumin to anhydrous ethanol is 1g:50mL~100mL, the ultrasonic treatment temperature is 40℃, the frequency is 40kHz, the power is 200W, and the time is 15min; the heating temperature of the epigallocatechin gallate aqueous solution is 60℃; the dropping rate of the curcumin ethanol solution is 1mL / min, the temperature is maintained at 60℃ during the dropping process, the stirring speed is 800rpm, and stirring continues for 30min after the dropping is completed.
[0014] In one embodiment of the present invention, in step two, the mass-to-volume ratio of chitosan to deionized water is 1.0 g / L to 3.0 g / L, the amount of glacial acetic acid added is sufficient to fully dissolve the chitosan, the stirring time is greater than or equal to 12 h, and the mass ratio of Tween 80 to chitosan is 0.1:1 to 0.5:1.
[0015] In one embodiment of the present invention, in step four, the mass-to-volume ratio of sodium alginate to deionized water is 0.5 g / L-2.0 g / L; the mass-to-volume ratio of oxidized sodium alginate to deionized water is 0.2 g / L-0.6 g / L; the mass-to-volume ratio of zinc sulfate to deionized water is 0.05 g / L-0.3 g / L; the dropping rate of the chitosan solution is 3 mL / min, the stirring speed is 1200 rpm; the dropping rate of the oxidized sodium alginate solution is 1 mL / min, the reaction temperature is 25℃-30℃; the dropping rate of the zinc sulfate solution is 1 mL / min, and stirring continues for 90 min after the zinc sulfate is added.
[0016] In one embodiment of the present invention, in step five, the centrifugation speed is 8000 rpm, the centrifugation time is 20 min, and the washing is performed three times; the mass ratio of trehalose to chitosan is 1:3 to 1:5; in step six, the inlet air temperature of the spray drying is 140℃-150℃, the outlet air temperature is 70℃-80℃, the feed rate is 5 mL / min-8 mL / min, and the atomization pressure is 0.15 MPa-0.20 MPa.
[0017] The beneficial effects of this invention are mainly reflected in the following aspects.
[0018] First, by constructing a chitosan-sodium alginate-oxidized sodium alginate ternary interpenetrating network, the structural stability of the nanoparticles was significantly improved through the synergistic effect of electrostatic interactions, Schiff base chemical bonds, and zinc ion coordination. The imine bonds formed by the aldehyde groups of oxidized sodium alginate and the amino groups of chitosan provide chemical cross-linking points, avoiding the dissociation risk during storage and application of purely physical adsorption structures. Zinc ions, acting as a bridging agent, coordinate with multiple functional groups to form a cross-linked network, further enhancing structural rigidity. This synergistic effect of multiple mechanisms enables the nanoparticles to maintain good dispersibility and stability over a wide pH range from 4 to 7, overcoming the problem of easy aggregation of protein nanoparticles in existing technologies.
[0019] Secondly, a hybrid loading strategy combining chemical cross-linking and physical encapsulation was employed to achieve highly efficient encapsulation of curcumin. Curcumin first forms a nanoscale complex with epigallocatechin gallate through hydrophobic interactions; this pre-complexation process significantly improves the dispersibility of curcumin in the aqueous phase. Subsequently, this complex is embedded into the hydrophobic microdomains of the polyelectrolyte complex through hydrophobic interactions, achieving physical encapsulation. More importantly, the β-diketone structure of curcumin can form stable chelate coordination with zinc ions, providing additional chemical anchoring. This synergy between physical encapsulation and chemical anchoring results in an encapsulation efficiency of over 85%, significantly higher than that of purely physical encapsulation methods.
[0020] Third, the introduction of epigallocatechin gallate as a synergistic antioxidant significantly enhances the antioxidant activity of the system through electron transfer and hydrogen bonding synergistic mechanisms. The enol structure of curcumin and the catechin structure of epigallocatechin gallate scavenge free radicals through hydrogen atom transfer and single-electron transfer mechanisms, respectively; when used in combination, their antioxidant activity can be increased by 30% to 40%. Simultaneously, the polyphenolic hydroxyl groups of epigallocatechin gallate can form a broad hydrogen bond network with the hydrophilic groups of chitosan and sodium alginate, enhancing the interaction between the active ingredient and the carrier and reducing the leakage of the active ingredient.
[0021] Fourth, the use of spray drying technology to prepare rehydrateable dry powder products solves the problems of poor storage stability and high transportation costs of aqueous nanoparticle dispersions. Trehalose, as a cryoprotectant, protects the nanoparticle structure during drying through a hydrogen bond replacement mechanism, preventing irreversible aggregation. After rehydration, the nanoparticle size of the spray-dried product increases by no more than 20%, maintaining good dispersibility. The dry powder form allows this preservative to be used in various preservation methods such as spraying, coating, and soaking, making its application more flexible and diverse.
[0022] Fifth, all components are food-grade materials, complying with China's GB2760-2014 standard for the use of food additives and GB9685-2016 standard for food contact materials. Sodium oxidized alginate, as a food-grade derivative of sodium alginate, has been proven to have good biocompatibility and safety, and can be directly applied to the preservation of fruits, vegetables, meat, aquatic products, and other foods. Detailed Implementation
[0023] The present invention will be further described in detail below with reference to specific embodiments. It should be noted that these embodiments are only used to illustrate the present invention and do not limit the scope of protection of the present invention.
[0024] Example 1 This embodiment provides a method for preparing a chitosan-curcumin nanocomposite preservative.
[0025] First, a curcumin-epigallocatechin gallate complex was prepared. 0.5 g of curcumin was dissolved in 25 mL of anhydrous ethanol and subjected to ultrasonic treatment in a 40 °C water bath. The ultrasonic frequency was set to 40 kHz, the power to 200 W, and the treatment time to 15 min, ensuring complete dissolution of the curcumin. Separately, 0.3 g of epigallocatechin gallate was dissolved in 25 mL of deionized water, heated to 60 °C, and stirred until completely dissolved. Under vigorous stirring at 800 rpm, the curcumin ethanol solution was added dropwise to the epigallocatechin gallate aqueous solution at a rate of 1 mL / min, maintaining the temperature at 60 °C during the addition. After the addition was complete, stirring was continued for 30 min to form a curcumin-epigallocatechin gallate nano-precursor dispersion. In this step, the phenolic hydroxyl groups of curcumin interact with the galloyl groups of epigallocatechin gallate through hydrogen bonds, while hydrophobic interactions drive the aggregation of curcumin molecules to form a core-shell precursor with a core rich in curcumin and an outer layer rich in epigallocatechin gallate, which significantly improves the dispersibility of curcumin in the aqueous phase.
[0026] Next, a chitosan solution was prepared. 1.5 g of chitosan powder with a degree of deacetylation of 90% and a molecular weight of 200 kDa was weighed and dispersed in 100 mL of deionized water. 1.5 mL of glacial acetic acid was added, and the mixture was stirred at room temperature for 12 h to allow it to fully swell and dissolve. The pH was then adjusted to 5.2 by adding 1 mol / L sodium hydroxide solution dropwise. 0.2 g of Tween 80 was then added as an emulsifier, and the mixture was stirred for another 30 min to ensure uniform dispersion, thus obtaining the chitosan solution. The addition of Tween 80 helps to stabilize the dispersion of the curcumin complex in the system.
[0027] Prepare the oxidized sodium alginate solution again. Weigh 0.4 g of oxidized sodium alginate (oxidation degree of 25%), dissolve it in 50 mL of deionized water, and stir at room temperature for 2 hours until completely dissolved to obtain the oxidized sodium alginate solution. This solution should be prepared immediately before use to avoid the aldehyde group undergoing self-condensation reaction during storage.
[0028] Next, the nanoparticles were prepared. 1.0 g of sodium alginate (molecular weight 350 kDa) was weighed and dissolved in 100 mL of deionized water, stirred until completely dissolved to obtain a sodium alginate solution. Separately, 0.15 g of zinc sulfate heptahydrate was weighed and dissolved in 50 mL of deionized water to obtain a zinc sulfate solution. Under vigorous stirring at 1200 rpm, a chitosan solution was added dropwise to the sodium alginate solution at a rate of 3 mL / min. The protonated amino groups of chitosan and the carboxyl groups of sodium alginate immediately formed a polyelectrolyte complex nanonucleus through electrostatic interaction. The driving force for this process was the enthalpy change of ion pair formation. According to the anti-ion condensation theory, polyelectrolytes with opposite charges can form a stable complex upon contact.
[0029] Immediately after the chitosan solution was added dropwise, the curcumin-epigallocatechin gallate nano-precursor dispersion was added to the system at a rate of 2 mL / min while maintaining vigorous stirring. The curcumin-epigallocatechin gallate complex intercalates into the hydrophobic microdomains of the polyelectrolyte complex through hydrophobic interactions and adsorbs onto its surface. Subsequently, sodium alginate oxidase solution was slowly added dropwise to the mixture at a rate of 1 mL / min, maintaining the temperature between 25°C and 30°C during the addition process. The aldehyde groups of sodium alginate oxidase react with the amino groups of chitosan through a Schiff base reaction to form imine bonds. This reaction can be carried out at pH 5 to 6 and room temperature, achieving a conversion rate of over 80% within 2 hours.
[0030] After the sodium alginate oxide solution was added, zinc sulfate solution was added dropwise to the system at a rate of 1 mL / min under continuous stirring. Zinc ions, as divalent metal cations, can simultaneously form octahedral coordination structures with the amino groups of chitosan, sodium alginate, and the carboxyl groups of sodium alginate oxide, and simultaneously form a 1:2 chelate coordination complex with the β-diketone group of curcumin. This coordination cross-linking network significantly improves the structural rigidity and chemical stability of the nanoparticles. After the zinc sulfate was added, stirring was continued for 90 min to allow the Schiff base reaction and coordination cross-linking to proceed fully, resulting in a nanoparticle suspension.
[0031] Then, the nanoparticles were purified. The nanoparticle suspension was centrifuged at 8000 rpm for 20 min, and the precipitate was collected. The precipitate was resuspended in deionized water, centrifuged again, and washed three times to remove unreacted raw materials and free active substances. After the final centrifugation, the precipitate was resuspended in 50 mL of deionized water, and 0.5 g of trehalose was added as a cryoprotectant. The mass ratio of trehalose to chitosan was 1:3, and the mixture was stirred thoroughly until it was completely dissolved.
[0032] Finally, spray drying was performed. The trehalose-containing nanoparticle suspension was transferred to a spray dryer with an inlet air temperature set at 145℃, an outlet air temperature set at 75℃, a feed rate of 6.5 mL / min, and an atomization pressure of 0.175 MPa. During spray drying, the nanoparticle suspension was atomized into tiny droplets, which were rapidly dehydrated under the action of hot air, forming micron-sized aggregates containing multiple nanoparticles. Trehalose, as a cryoprotectant, protected the nanoparticle structure during drying through a hydrogen bond replacement mechanism. Its hydroxyl groups can form hydrogen bonds with the hydrophilic groups of chitosan and sodium alginate, replacing the original hydrogen bonds between water molecules and polymers, thereby preventing irreversible aggregation of nanoparticles during dehydration. The dried powder was collected, sealed in a brown glass bottle, and stored in a refrigerator at 4℃ away from light to obtain the chitosan-curcumin nanocomposite preservative.
[0033] In the nanocomposite preservative prepared in this embodiment, the mass ratio of chitosan to sodium alginate is 1.5:1, the molar ratio of aldehyde groups to chitosan amino groups in oxidized sodium alginate is 1:12, the molar ratio of zinc ions to chitosan amino groups is 0.2:1, and the mass ratio of curcumin to epigallocatechin gallate is 1.67:1. This ratio is within the preferred range of the present invention.
[0034] Example 2 The difference between this embodiment and Embodiment 1 lies in the adjustment of the chitosan dosage, sodium alginate dosage, and related parameters to cover the endpoint values of the formulation.
[0035] The steps for preparing the curcumin-epigallocatechin gallate complex are the same as in Example 1. When preparing the chitosan solution, 3.0 g of chitosan powder with a degree of deacetylation of 95% and a molecular weight of 300 kDa was weighed, dispersed in 100 mL of deionized water, and dissolved by stirring with 3.0 mL of glacial acetic acid. The pH was adjusted to 5.0, and 0.5 g of Tween 80 was added. When preparing the sodium alginate oxidized solution, 0.6 g of sodium alginate oxidized with a degree of oxidation of 30% was weighed. When preparing the sodium alginate solution, 2.0 g of sodium alginate with a molecular weight of 500 kDa was weighed. The amount of zinc sulfate was increased to 0.3 g.
[0036] During the preparation of nanoparticles, the dropping rates of the chitosan solution, curcumin complex, sodium alginate oxidase solution, and zinc sulfate solution were the same as in Example 1. Other operating steps were the same as in Example 1.
[0037] In the nanocomposite preservative prepared in this embodiment, the mass ratio of chitosan to sodium alginate is 1.5:1. However, the amount of chitosan and sodium alginate reaches the upper limit of the formulation. The oxidation degree and amount of oxidized sodium alginate are both at the upper limit, as is the amount of zinc ions. The degree of deacetylation of chitosan is 95% (upper limit), and its molecular weight is 300 kDa (upper limit). The molecular weight of sodium alginate is 500 kDa (upper limit). These parameter settings verify the feasibility of the present invention under the endpoint conditions.
[0038] Example 3 This embodiment covers the other endpoint of the mass ratio of chitosan to sodium alginate.
[0039] When preparing the chitosan solution, 2.0 g of chitosan powder with a degree of deacetylation of 85% and a molecular weight of 100 kDa was weighed and dispersed in 100 mL of deionized water. 2.0 mL of glacial acetic acid was added and stirred to dissolve the powder. The pH was adjusted to 5.5, and 0.1 g of Tween 80 was added. When preparing the sodium alginate solution, 0.5 g of sodium alginate with a molecular weight of 200 kDa was weighed. When preparing the oxidized sodium alginate solution, 0.2 g of oxidized sodium alginate with an oxidation degree of 20% was weighed. 0.05 g of zinc sulfate was used. The amounts of curcumin and epigallocatechin gallate were the same as in Example 1.
[0040] The other preparation steps are the same as in Example 1. In this example, the mass ratio of chitosan to sodium alginate reaches the upper limit of 2:0.5, the oxidation degree and amount of sodium alginate are both at the lower limit, and the amount of zinc ions is at the lower limit. The degree of deacetylation of chitosan is 85% (lower limit), the molecular weight is 100 kDa (lower limit), the molecular weight of sodium alginate is 200 kDa (lower limit), and the amount of Tween 80 is at the lower limit.
[0041] Example 4 This embodiment covers the endpoint values of the mass ratio of curcumin to epigallocatechin gallate.
[0042] In preparing the curcumin-epigallocatechin gallate complex, the amount of curcumin used was 0.6 g, and the amount of epigallocatechin gallate was 0.3 g, with a mass ratio of 2:1. The ultrasonic treatment temperature, time, power, and subsequent operations were the same as in Example 1.
[0043] The amount of chitosan used was 1.8g, with a degree of deacetylation of 88% and a molecular weight of 150kDa; the amount of sodium alginate used was 1.2g, with a molecular weight of 300kDa; the amount of oxidized sodium alginate used was 0.3g, with an oxidation degree of 22%; the amount of zinc sulfate used was 0.18g; and the amount of Tween 80 used was 0.3g. Other preparation steps were the same as in Example 1.
[0044] Example 5 This embodiment covers the endpoint values of spray drying parameters.
[0045] The preparation process of the nanoparticles was the same as in Example 1. In the spray drying step, the inlet air temperature was set to 140°C, the outlet air temperature to 70°C, the feed rate to 5 mL / min, and the atomization pressure to 0.15 MPa. The mass ratio of trehalose to chitosan was adjusted to 1:5. These parameters cover the lower limits of the spray drying process.
[0046] Example 6 This embodiment covers the other endpoint value of the spray drying parameters.
[0047] The preparation process of the nanoparticles was the same as in Example 2. In the spray drying step, the inlet air temperature was set to 150°C, the outlet air temperature to 80°C, the feed rate to 8 mL / min, and the atomization pressure to 0.20 MPa. The trehalose dosage was adjusted to a mass ratio of 1:3.5 to the solids. These parameters cover the upper limits of the spray drying process.
[0048] Comparative Example 1 This comparative example does not include sodium oxidized alginate to verify the contribution of Schiff base chemical crosslinking to the stability of nanoparticles.
[0049] The preparation process is basically the same as in Example 1, but the preparation and addition steps of sodium alginate oxidase solution are omitted. After mixing chitosan solution and sodium alginate solution to form a polyelectrolyte complex, and adding curcumin-epigallocatechin gallate complex, zinc sulfate solution is directly added for coordination crosslinking, while other steps remain unchanged.
[0050] This comparative example relies solely on two mechanisms: electrostatic interaction and zinc ion coordination, lacking Schiff base chemical crosslinking. It is used to compare and verify the importance of chemical crosslinking for structural stability.
[0051] Comparative Example 2 This comparative example does not contain zinc ions to verify the contribution of coordination crosslinking to the stability of nanoparticles and curcumin fixation.
[0052] The preparation process was basically the same as in Example 1, but the preparation and addition steps of the zinc sulfate solution were omitted. After the sodium alginate oxidase solution was added and reacted for 90 minutes, centrifugation purification was performed directly, while other steps remained unchanged.
[0053] This comparative example relies solely on two mechanisms: electrostatic interaction and Schiff base reaction. It lacks zinc ion coordination crosslinking, and curcumin cannot form chelate coordination with zinc ions through β-diketone groups. This is used to verify the necessity of coordination crosslinking.
[0054] Comparative Example 3 This comparative example does not contain epigallocatechin gallate; only curcumin is used as the active ingredient to verify the synergistic antioxidant mechanism.
[0055] In the preparation process, 0.5 g of curcumin was directly dissolved in 50 mL of ethanol, and after ultrasonic treatment, it was used directly without pre-complexation with epigallocatechin gallate. The dosage of other components and the preparation steps were the same as in Example 1, except that the curcumin ethanol solution was added directly to the system after the polyelectrolyte complex was formed.
[0056] To fully evaluate the technical effects of the present invention, the above embodiments and comparative examples were systematically tested.
[0057] Particle size and Zeta potential determination. The particle size distribution and Zeta potential of the nanoparticles after rehydration were determined using dynamic light scattering. 10 mg of dried powder was dispersed in 10 mL of pH 5.5 buffer solution and ultrasonically dispersed for 5 min before measurement. Particle size was measured at 25℃ with a detection angle of 90 degrees, and each sample was measured three times. Zeta potential was determined using electrophoretic light scattering under identical conditions.
[0058] Encapsulation efficiency determination. The encapsulation efficiency of curcumin and epigallocatechin gallate was determined by centrifugation. The nanoparticle suspension was centrifuged at 12000 rpm for 30 min, and the supernatant and precipitate were separated. Free curcumin and epigallocatechin gallate in the supernatant were quantified by high-performance liquid chromatography (HPLC). The detection wavelength for curcumin was 425 nm, and the detection wavelength for epigallocatechin gallate was 280 nm. The encapsulation efficiency was calculated as follows: encapsulation efficiency equals the mass of active ingredient in the precipitate divided by the total feed amount multiplied by 100%.
[0059] Antioxidant activity assay. The DPPH free radical scavenging method was used to evaluate antioxidant activity. A 0.1 mmol / L DPPH ethanol solution was prepared, and 0.1 mL of the sample solution was added to 3.9 mL of DPPH solution. The reaction was carried out at room temperature in the dark for 30 min, and the absorbance was measured at 517 nm. The free radical scavenging rate was calculated as follows: the scavenging rate equals the difference between the blank absorbance and the sample absorbance, divided by the blank absorbance multiplied by 100%. The sample concentration was uniformly set to 1 mg / mL.
[0060] pH-responsive controlled-release assay. The release behavior of nanoparticles under different pH conditions was studied using dialysis. 10 mg of sample was dispersed in 5 mL of release medium, placed in a dialysis bag with a molecular weight cutoff of 8000 to 14000 Da, and then placed in 100 mL of release medium. The mixture was incubated at 37°C with constant shaking at 100 rpm. Two release media were prepared at pH 5.0 and pH 7.4, and the curcumin concentration in the release media was measured periodically to calculate the cumulative release rate.
[0061] Storage stability determination. The dried powder was stored in the dark at 4℃ and 25℃ respectively. Samples were taken every 7 days to measure changes in particle size and encapsulation efficiency, and the monitoring was carried out continuously for 28 days.
[0062] The test results are shown in Tables 1 and 2.
[0063] Table 1 Physicochemical properties of nanoparticles sample Particle size (nm) Zeta potential (mV) Curcumin encapsulation rate (%) EGCG encapsulation rate (%) Curcumin loading (%) EGCG drug loading (%) Example 1 225±12 +30.2±1.8 87.3±2.1 78.5±1.9 10.2±0.3 6.5±0.2 Example 2 268±15 +32.5±2.1 89.1±1.8 80.2±2.2 11.8±0.4 7.8±0.3 Example 3 178±10 +28.6±1.5 85.8±2.3 75.3±2.0 8.3±0.3 5.2±0.2 Example 4 235±13 +29.8±1.7 88.5±2.0 79.1±1.8 10.8±0.3 6.8±0.2 Example 5 242±14 +29.5±1.9 86.9±2.2 77.8±2.1 9.9±0.4 6.3±0.3 Example 6 255±16 +31.3±2.0 88.8±1.9 79.8±1.9 11.5±0.4 7.5±0.3 Comparative Example 1 285±22 +26.3±2.5 72.5±3.8 65.2±3.5 7.8±0.6 4.9±0.5 Comparative Example 2 258±18 +27.8±2.3 75.8±3.2 68.5±3.0 8.5±0.5 5.4±0.4 Comparative Example 3 232±13 +30.5±1.8 84.2±2.4 - 9.8±0.3 - As shown in Table 1, the particle size of the nanocomposite preservatives prepared in Examples 1 to 6 of this invention is controlled within the range of 150 nm to 300 nm, and the Zeta potential is between +25 mV and +35 mV, indicating that the nanoparticles have good dispersibility and electrostatic stability. The encapsulation efficiency of curcumin is greater than 85%, and the encapsulation efficiency of epigallocatechin gallate is greater than 75%, verifying the high efficiency of the mixed loading strategy of this invention. In Comparative Example 1, due to the lack of Schiff base chemical crosslinking, the nanoparticle size is larger and the encapsulation efficiency is significantly reduced, indicating that chemical crosslinking plays an important role in maintaining the compactness of the nanoparticle structure and improving the encapsulation efficiency. In Comparative Example 2, due to the lack of zinc ion coordination crosslinking, the encapsulation efficiency is also significantly reduced, because curcumin cannot obtain additional chemical anchoring by chelating with zinc ions through β-diketone groups. Although the encapsulation efficiency of Comparative Example 3 is acceptable, it lacks the synergistic effect of epigallocatechin gallate.
[0064] Table 2 Antioxidant activity and controlled-release performance sample DPPH clearance rate (%) Release rate (%) at pH 5.0-24h pH 7.4 - 24h release rate (%) Encapsulation retention rate (%) at 25℃-28d Example 1 82.5±2.3 27.3±1.8 73.5±2.5 91.2±1.5 Example 2 84.8±2.1 24.8±1.5 76.2±2.8 93.5±1.3 Example 3 79.8±2.5 29.5±2.0 71.2±2.3 88.6±1.8 Example 4 83.2±2.2 26.5±1.7 74.8±2.6 92.0±1.4 Example 5 81.5±2.4 28.2±1.9 72.8±2.4 90.3±1.6 Example 6 83.9±2.3 25.8±1.6 75.5±2.7 92.8±1.5 Comparative Example 1 76.2±3.2 35.8±2.8 82.5±3.5 78.5±2.8 Comparative Example 2 74.5±3.5 38.2±3.0 85.3±3.8 75.3±3.2 Comparative Example 3 58.3±3.8 26.8±1.8 73.8±2.6 89.5±1.7 Table 2 shows that the DPPH free radical scavenging rate of the embodiments of the present invention is greater than 79%, significantly higher than that of Comparative Example 3 (58.3%), fully demonstrating the effectiveness of the synergistic antioxidant effect of curcumin and epigallocatechin gallate. This is because curcumin mainly scavenges free radicals through a hydrogen atom transfer mechanism, while epigallocatechin gallate mainly functions through a single electron transfer mechanism. The complementary nature of these two mechanisms significantly enhances the antioxidant activity. Although Comparative Examples 1 and 2 contain two antioxidants, their poor structural stability led to leakage of some active ingredients during the testing process, resulting in a decrease in antioxidant activity.
[0065] Controlled-release performance tests showed that the nanocomposite preservative of this invention exhibits significant pH responsiveness. Under acidic conditions (pH 5.0), the cumulative release rate over 24 hours was controlled between 24.8% and 29.5%, while under weakly alkaline conditions (pH 7.4), the cumulative release rate reached 71.2% to 76.2% over 24 hours. This pH responsiveness stems from the pH-sensitive properties of chitosan. In acidic environments, the degree of amino protonation of chitosan increases, enhancing its electrostatic interaction with sodium alginate, resulting in a compact nanoparticle structure and slow release of the active ingredient. In neutral or weakly alkaline environments, chitosan deprotonates, weakening the electrostatic interaction, causing particle swelling, and accelerating the release of the active ingredient. Comparative Examples 1 and 2 showed weaker pH responsiveness, with no significant difference in release under the two pH conditions. This is because the lack of chemical or coordination crosslinking resulted in a loose structure, which could not effectively maintain structural compactness under acidic conditions.
[0066] Storage stability tests showed that the encapsulation retention rate of the embodiments of the present invention was greater than 88% after storage at 25°C for 28 days, indicating that the spray-dried powder has good storage stability. Trehalose, as a cryoprotectant, effectively protected the nanoparticle structure through a hydrogen bond replacement mechanism. The encapsulation retention rates of Comparative Examples 1 and 2 were significantly lower, which is due to poor structural stability and easy leakage of active ingredients during storage.
[0067] Based on the above test results, it can be seen that this invention has successfully prepared a nanocomposite preservative with stable structure, high encapsulation efficiency, strong antioxidant activity, and pH-responsive controlled release performance by constructing a chitosan-sodium alginate-oxidized sodium alginate ternary interpenetrating network and utilizing the synergistic effect of electrostatic interaction, Schiff base chemical crosslinking, and zinc ion coordination.
[0068] The technical advantages of this invention are not only reflected in the data advantages, but more importantly, in the rationality of its internal mechanism. The polyelectrolyte complex formed by chitosan and sodium alginate provides basic electrostatic stability, which is a prerequisite for the rapid formation of nanoparticles. The introduction of oxidized sodium alginate achieves chemical cross-linking. The imine bond formed by its aldehyde group and the amino group of chitosan is a covalent bond with a bond energy much higher than that of hydrogen bonds and electrostatic interactions, thus maintaining stability over a wide pH range and temperature conditions. More importantly, zinc ions, as a bridging agent, have a dual significance in their coordination effect. On the one hand, zinc ions can simultaneously coordinate with multiple functional groups to form a three-dimensional cross-linked network, enhancing structural rigidity. On the other hand, the chelation coordination between zinc ions and the β-diketone group of curcumin provides a chemical anchoring site for the active ingredient, allowing curcumin to be fixed to the carrier not only through physical embedding but also through chemical bonding, significantly reducing the risk of leakage.
[0069] Furthermore, the synergistic effect of curcumin and epigallocatechin gallate also has a profound chemical basis. The β-diketone structure in curcumin exhibits enol-keto tautomerism in solution, and the enol phenolic hydroxyl group provides active hydrogen for free radical scavenging. The catechin structure in epigallocatechin gallate has multiple adjacent hydroxyl groups, which can form semiquinone free radicals through electron delocalization, thereby scavenging reactive oxygen species. When used together, curcumin preferentially scavenge lipophilic free radicals, while epigallocatechin gallate preferentially scavenge hydrophilic free radicals, covering the free radical scavenging needs in different polar environments, thus significantly enhancing antioxidant activity. Simultaneously, the polyphenolic hydroxyl groups of epigallocatechin gallate can form extensive intermolecular hydrogen bonds with the hydroxyl and amino groups of chitosan and sodium alginate. These hydrogen bonds not only enhance the interaction between the active ingredient and the carrier but also help maintain the structural stability of the nanoparticles.
[0070] It is worth emphasizing that all components of this invention are food-grade materials, which is an important prerequisite for its practical application. Chitosan and sodium alginate are approved food additives. Oxidized sodium alginate, as an oxidized derivative of sodium alginate, degrades into phycouronic acid and glucose, both of which are natural carbohydrate metabolites and are non-toxic and harmless. Curcumin and epigallocatechin gallate are both natural plant extracts, and their long-term safety has been widely verified. Zinc, as an essential trace element for the human body, is added in amounts far below the upper limit for nutritional fortification in this invention. Therefore, the nanocomposite preservative prepared by this invention can be safely used for food preservation.
[0071] As can be clearly seen from the above detailed description, the chitosan-curcumin nanocomposite preservative and its preparation method provided by the present invention, through systematic innovation in material selection, structural design and process optimization, successfully solves the technical problems of poor stability of nanocarrier structure, low encapsulation efficiency of active ingredients and single application form in the prior art, and achieves efficient, stable and safe food preservation effect, and has good application prospects.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A chitosan-curcumin nanocomposite preservative, characterized in that: The nanoparticles include a chitosan-sodium alginate-sodium oxidized alginate interpenetrating network structure. The nanoparticles form a polyelectrolyte complex core through the protonated amino groups of chitosan and the carboxyl groups of sodium alginate. The aldehyde groups of sodium oxidized alginate react with the amino groups of chitosan through a Schiff base reaction to form a chemical cross-linking network. Zinc ions form coordination cross-links with the amino groups of chitosan, the carboxyl groups of sodium alginate, and the carboxyl groups of sodium oxidized alginate. Curcumin and epigallocatechin gallate form a complex through hydrogen bonding and hydrophobic interactions. The complex is embedded in the interpenetrating network structure. The β-diketone group of curcumin forms a chelate coordination with zinc ions.
2. The chitosan-curcumin nanocomposite preservative according to claim 1, characterized in that: The chitosan has a degree of deacetylation of 85%–95% and a molecular weight of 100kDa–300kDa; the sodium alginate has a molecular weight of 200kDa–500kDa; and the oxidized sodium alginate has an oxidation degree of 20%–30%.
3. The chitosan-curcumin nanocomposite preservative according to claim 1, characterized in that: The mass ratio of chitosan to sodium alginate is 1.0:0.5 to 2.0:1.0; the molar ratio of aldehyde groups to chitosan amino groups in the oxidized sodium alginate is 1:15 to 1:10; the molar ratio of zinc ions to chitosan amino groups is 0.1:1 to 0.3:1; and the mass ratio of curcumin to epigallocatechin gallate is 1.5:1 to 2.0:
1.
4. The chitosan-curcumin nanocomposite preservative according to claim 1, characterized in that: The nanoparticles have a particle size of 150nm-300nm, a zeta potential of +25mV to +35mV, an encapsulation efficiency of curcumin greater than or equal to 85%, an encapsulation efficiency of epigallocatechin gallate greater than or equal to 75%, a drug loading of curcumin of 8% to 12%, and a drug loading of epigallocatechin gallate of 5% to 8%.
5. The chitosan-curcumin nanocomposite preservative according to claim 1, characterized in that: The preservative is a spray-dried powder with a moisture content of less than or equal to 5%, and trehalose is added as a cryoprotectant. The mass ratio of trehalose to solids is 1:3 to 1:
5. After rehydration, the nanoparticle size of the powder increases by no more than 20%.
6. The preparation method of the chitosan-curcumin nanocomposite preservative according to claim 1, characterized in that... Includes the following steps: Step 1: Dissolve curcumin in anhydrous ethanol and sonicate to obtain curcumin ethanol solution; dissolve epigallocatechin gallate in deionized water and heat to obtain epigallocatechin gallate aqueous solution; add the curcumin ethanol solution dropwise to the epigallocatechin gallate aqueous solution under stirring to form curcumin-epigallocatechin gallate nano precursor dispersion. Step 2: Disperse chitosan powder in deionized water, add glacial acetic acid and stir to dissolve, adjust the pH value to 5.0-5.5, add Tween 80 and stir to mix, to obtain chitosan solution; Step 3: Dissolve sodium oxidized alginate in deionized water and stir until completely dissolved to obtain sodium oxidized alginate solution; Step 4: Dissolve sodium alginate in deionized water to obtain a sodium alginate solution; dissolve zinc sulfate in deionized water to obtain a zinc sulfate solution; The chitosan solution was added dropwise to the sodium alginate solution under stirring conditions to form a polyelectrolyte complex nanonucleus; The curcumin-epigallocatechin gallate nanoprecursor dispersion was added to the polyelectrolyte complex nanocore; then the sodium alginate oxidase solution was added to carry out a Schiff base reaction; then zinc sulfate solution was added to carry out coordination crosslinking, and the reaction was stirred to obtain a nanoparticle suspension. Step 5: Centrifuge the nanoparticle suspension to collect the precipitate, wash it with deionized water, resuspend it in deionized water, add trehalose and stir to mix. Step six: Spray dry the trehalose-containing nanoparticle suspension and collect the dried powder.
7. The preparation method according to claim 6, characterized in that: In step one, the mass-to-volume ratio of curcumin to anhydrous ethanol is 1g:50mL~100mL. The ultrasonic treatment temperature is 40℃, the frequency is 40kHz, the power is 200W, and the time is 15min. The heating temperature of the epigallocatechin gallate aqueous solution is 60℃. The dropping rate of the curcumin ethanol solution is 1mL / min. During the dropping process, the temperature is maintained at 60℃, the stirring speed is 800rpm, and stirring continues for 30min after the dropping is completed.
8. The preparation method according to claim 6, characterized in that: In step two, the mass-to-volume ratio of chitosan to deionized water is 1.0 g / L-3.0 g / L, the amount of glacial acetic acid added is sufficient to fully dissolve the chitosan, the stirring time is greater than or equal to 12 h, and the mass ratio of Tween 80 to chitosan is 0.1:1 to 0.5:
1.
9. The preparation method according to claim 6, characterized in that: In step four, the mass-to-volume ratio of sodium alginate to deionized water is 0.5 g / L-2.0 g / L; the mass-to-volume ratio of oxidized sodium alginate to deionized water is 0.2 g / L-0.6 g / L; the mass-to-volume ratio of zinc sulfate to deionized water is 0.05 g / L-0.3 g / L; the dropping rate of the chitosan solution is 3 mL / min, the stirring speed is 1200 rpm; the dropping rate of the oxidized sodium alginate solution is 1 mL / min, the reaction temperature is 25℃-30℃; the dropping rate of the zinc sulfate solution is 1 mL / min, and stirring continues for 90 min after the zinc sulfate is added.
10. The preparation method according to claim 6, characterized in that: In step five, the centrifugation speed is 8000 rpm, the centrifugation time is 20 min, and the washing is performed three times; the mass ratio of trehalose to chitosan is 1:3 to 1:5; in step six, the inlet air temperature of spray drying is 140℃-150℃, the outlet air temperature is 70℃-80℃, the feed rate is 5mL / min-8mL / min, and the atomization pressure is 0.15MPa-0.20MPa.
Citation Information
Patent Citations
Layer-by-layer nanoparticle filling type fresh-keeping-indicating composite film as well as preparation method and application thereof
CN116023716A
Cited By
Chitosan-chlamydomonas reinhardtii protein composite carrier as well as preparation method and application thereof
CN122074651A
A chitosan-Chlamydomonas reinhardtii protein composite carrier, its preparation method and application
CN122074651B